Design and Synthesis of Angularly Annulated Spirocyclics via Enyne Metathesis and the Diels–Alder Reaction as Key Steps - Kotha, Sambasivarao; Ali, Rashid; Tiwari, Arti (Synthesis, 2014)
We have developed a simple and an efficient route to a range of angularly fused spirocycles by the application of enyne metathesis and the Diels–Alder reaction as key steps. The enyne metathesis protocol has been further extended to the dibenzylation of indane-1,3-dione by using cross-enyne metathesis in the presence of hexa-1,5-diene with the aid of Grubbs’ 1st generation catalyst followed by an aromatization sequence with DDQ.
Keywords: active methylene compounds; cross-metathesis; Diels–Alder reaction; enyne metathesis; spirocyclic compounds